Cadmium (Cd) tolerance evaluation of three strains of microalgae of the genus Ankistrodesmus, Chlorella and Scenedesmus - D. Duque; C. Montoya; L. R. Botero (Revista Facultad de Ingeniería Universidad de Antioquia, 2019)
In order to assess tolerance to cadmium (Cd) for three Colombian native strains of microalgae belonging to the genus Ankistrodesmus, Chlorella and Scenedesmus the growth kinetics, the concentration of pigments, the total dry weight in media contaminated with cadmium in ranges between 0.0 - 15.0 mg L-1 , and the median lethal concentration (LC50) were determined. Additionally, for the more tolerant strains, Scenedesmus sp. and Chlorella sp., removal of Cd in media enriched with 1.0 and 7.0 mg L-1 contaminant was quantified. The study found that Scenedesmus sp was the strain that had the highest tolerance to cadmium generating 36.15 µg mL-1 of dry biomass at 3.5 mg L-1 of Cd and LC50 20.89 mg L-1 Cd after 12 days of culture. The highest percentage of removal of cadmium was 32% for Scenedesmus sp. Chlorella sp. presented good removal of Cd in cultures with low levels of metal and Ankistrodesmus sp. was the microalgae with less tolerance.